Medeae Medea forem' : rehabilitating Ovid's Medea - Flanders, Bethany Leigh (Trinity College (Dublin, Ireland). Department of Classics, 2016)
This project concerns itself with the characterisation of Ovid's Medea, as she appears in the twin letters Heroides 6 and 12, and in Book 7 of the Metamorphoses. The thesis argues first that the Ovidian Medea can be read as an example of coherent and persuasive characterisation; second, that the poet depicts Medea as one consistent personality-type in both the Heroides and the Metamorphoses. This reading stands in opposition to the prevailing scholarly assessment of Medea, which holds that she is one of Ovid's least successful characterisations, and that the poet develops her character very differently in his epic and elegiac narratives. The premise ofthe thesis is that the so called 'difficulties' with Ovid's characterisation of Medea arise from the critic's assumptions about how the heroine should think, feel and behave within the Ovidian sphere. The project argues that Medea shows consistency in her modes of thinking and reasoning across her Ovidian texts, but that this is apparent only if the reader sets out to examine the ways in which Ovid's heroine differs from those of the preceding Greek tradition. Specifically, the reading suggests that Ovid’s Medea lacks the moral stature of the heroines of Apollonius and Euripides: she is self-focused and unsympathetic, driven by the desire to possess and exercise control over the other characters of her myth.
Keywords: Classics, Ph.D.; PhD Trinity College Dublin, 2016